Pengaruh digital financial literacy, financial skill, financial stress dan financial self-efficacy terhadap financial well-being: Studi lintas generasi di Provinsi Riau - Tanjung, Andini; Muat, Susnaningsih (Jurnal Ilmu Manajemen, 2025)
Differences in financial characteristics across generations influence individual financial well-being. In the rapidly evolving digital era, digital financial literacy has become a crucial factor in financial management. This study aims to analyze the influence of digital financial literacy, financial skills, financial stress, and financial self-efficacy on financial well-being among Generations X, Y, and Z in Riau Province. Data were collected through questionnaires, and intergenerational differences were examined. The results indicated significant differences in financial well-being, digital financial literacy, and financial stress across generations; however, no significant differences were found in financial skills and financial self-efficacy. Digital financial literacy positively and significantly influenced financial well-being in Generation Z, whereas no significant impact was observed in Generations X and Y. Financial skills had a significant positive impact on financial well-being across all three generations. Conversely, financial stress negatively and significantly affected financial well-being across generations, while financial self-efficacy contributed positively. These findings highlight the importance of digital financial literacy and effective financial management skills in enhancing financial well-being. They also underline the necessity for tailored approaches to address financial stress within each generation. This study provides valuable insights for policymakers and financial education institutions.